Lawyer's world and childhood dreams - Yatindra Singh (Allahabad, 2000)
The books witty style makes these strings of anecdotes worth a read. The author draws together interesting incidents form this career as also exemplary personalities he had come across in his yeas as a legal eagle.
Keywords: Law